Promising integrated farming systems for dryland agro-ecosystems - Gopinath, K. A.; Bhargavi, B.; Kumari, V. Visha; Venkatesh, G.; Singh, V. K. (Indian Farming, 2025)
Rainfed agriculture, predominant in arid, semi-arid and sub-humid regions of the country, plays a crucial role in sustaining the economy and food security of India. At present, about 51% of the net sown area is rainfed contributing to 41% of the total food production and supporting 40% of human and 60% of livestock population. Low agricultural productivity, soil degradation andother factors, both endogenic (e.g. land size, water, cultural, and demographic) and exogenic (e.g. weather, markets, and migration) are pervasive constraints in the dryland smallholder farming systems of India. There is a need to address agricultural productivity to meet the needs of the growing population and enable sustainable rural livelihoods in the dryland regions. The location specific integrated farming systems (IFS) are important and relevant especially for the small and marginal farmers as they are more resilient, productive and adaptive to climate variability. The IFS approach also has the potential to overcome multifarious problems of farmers including resource degradation, declining resource use efficiency, farm productivity and profitability.